2022
DOI: 10.3390/nano12061014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Radial Stress on the Nanoparticle-Based Electrolyte Layer in a Center-Wound Roll with Roll-to-Roll Systems

Abstract: Recently, slot-die coating based on the roll-to-roll process has been actively used to fabricate nanoparticle-based electrolyte layers because it is advantageous for high-speed processes and mass production of uniformly thick electrolyte layers. In this process, the fabricated electrolyte layer is stored as a wound roll throughout the rewinding process. We analyzed the defects and geometric changes in an electrolyte layer, i.e., gadolinium-doped cerium oxide (GDC), due to the radial stress in the wound roll. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…In this process, many webs are wound on one central core in the final product, thereby increasing productivity; however, the quality of the functional layer may be degraded if excessive radial stress is generated within the wound roll. Noh et al observed that radial stress increased over time due to residual stress and reported that the storage time of a wound roll needs to be minimized [ 27 ]. In particular, when the electrolyte layer manufactured by Roll-to-Roll slot die coating is stored in a compact wound roll form, it is confirmed that the thickness of the electrolyte layer decreases due to the excessive stress in a radial and hoop direction generated inside the wound roll as a large amount of web is wound.…”
Section: Introductionmentioning
confidence: 99%
“…In this process, many webs are wound on one central core in the final product, thereby increasing productivity; however, the quality of the functional layer may be degraded if excessive radial stress is generated within the wound roll. Noh et al observed that radial stress increased over time due to residual stress and reported that the storage time of a wound roll needs to be minimized [ 27 ]. In particular, when the electrolyte layer manufactured by Roll-to-Roll slot die coating is stored in a compact wound roll form, it is confirmed that the thickness of the electrolyte layer decreases due to the excessive stress in a radial and hoop direction generated inside the wound roll as a large amount of web is wound.…”
Section: Introductionmentioning
confidence: 99%